2015
DOI: 10.1144/sp433.7
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Last Glacial Maximum across the Anatolian peninsula

Abstract: Uludağ is a prominent mountain in northwestern Turkey where glacial deposits have been documented in the Kovuk Valley and the glacial history has been reconstructed based on 31 cosmogenic 10Be exposure ages from glacially transported boulders and bedrock. The results suggest that the Kovuk Glacier began advancing before 26.5±1.6 ka. It reached its maximum extent at 20.3±1.3 ka, followed by a re-advance at 19.3±1.2 ka, both during the global Last Glacial Maximum (LGM) within Marine Isotope Stage 2. The timing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…These are either 10 Be or 36 Cl exposure age studies. As reviewed by Sarıkaya & Ç iner (2015) and Akçar et al (2015) in this volume, all of these data indicate Late Pleistocene glaciation in Turkey. In marked contrast with the records in Greece, Italy and the western Mediterranean, there is currently no published evidence of older Middle Pleistocene glaciations anywhere in Turkey.…”
Section: Turkey and The Near Eastmentioning
confidence: 76%
See 2 more Smart Citations
“…These are either 10 Be or 36 Cl exposure age studies. As reviewed by Sarıkaya & Ç iner (2015) and Akçar et al (2015) in this volume, all of these data indicate Late Pleistocene glaciation in Turkey. In marked contrast with the records in Greece, Italy and the western Mediterranean, there is currently no published evidence of older Middle Pleistocene glaciations anywhere in Turkey.…”
Section: Turkey and The Near Eastmentioning
confidence: 76%
“…The timing of glaciations in the Mediterranean mountains has been constrained using a range of approaches. Examples presented in this volume include cosmogenic nuclide exposure dating of boulders and bedrock surfaces (Akçar et al 2015;Federici et al 2016;Palacios et al 2016;Pope et al 2015;Turu et al 2016), radiocarbon dating of basal glacial lake deposits (Giraudi & Giaccio 2015;Serrano et al 2016;Turu et al 2016), Ar/Ar dating of tephras in mountain basins (Giraudi & Giaccio 2015), optically stimulated luminescence dating of glacio-fluvial outwash deposits (Serrano et al 2016;Turu et al 2016) and uranium series dating of secondary carbonate cements Serrano et al 2016) in glacial and glacio-fluvial deposits.…”
Section: The Glacial Pioneersmentioning
confidence: 99%
See 1 more Smart Citation
“…If we take into consideration evidence of local and regional glacial advances in the Pleistocene, few studies describe the extent of glaciers on the Mount Ararat/Ağri Daği. Çiner (2004), Sarikaya et al (2011), Sarikaya and Çiner (2014), and Akçar et al (2015) reported evidence for wide Pleistocene glaciations in the Taurus Mountains, on the northern-facing slopes of the Eastern Black Sea Mountains, on the Mounts Erciyes and Süphan, and on Mount Ararat/Ağri Daği; for the LGM they identified a mean snow line altitude at ca. 2500 m a.s.l.…”
Section: Previous Geomorphological and Glaciological Studiesmentioning
confidence: 99%
“…In the last two decades, quantitative palaeoglacier studies in Turkey have witnessed an unprecedented increase (Hughes et al, 2013;Hughes and Woodward, 2017), thanks to the application of cosmogenic nuclide surface dating methods (e.g. Akçar et al, 2007Akçar et al, , 2017Sarıkaya et al, 2008Sarıkaya et al, , 2014Sarıkaya and Çiner, 2017, and references therein).…”
Section: Introductionmentioning
confidence: 99%